Contracting-Out Asset Maintenance: How Arrangements Adapt Over Time - Furneaux, C.; Brown, Kerry; Ryan, N.; Gudmundsson, A.; Tywoniak, Stephane (Institute of Electrical and Electronics Engineers ( IEEE ), 2009)
Contracting-out and privatisation are key drivers of organisational and market change, which, along with technological and societal change, are “creating a new generation of infrastructures”. While new institutional arrangements have the potential to improve maintenance efficiency through consistent and repeatable patterns of action - unanticipated difficulties in implementation can reduce the performance of these arrangements. Faced with unsatisfactory performance of contracting-out arrangements, government organisations may adapt and change these arrangements over time, with the aim of improving performance. This paper enhances our understanding of `next generation infrastructures' by examining adaptation of the organisational arrangements for the maintenance of these assets, in a case study spanning 20 years.